A human 3D BBB chip model of acute stroke simulating a reversible penumbra - Kyung A Kwak; Eun-Young Shin; Kyung Sik Yi; Chi-Hoon Choi (PLoS ONE, 2026)
Ischemic stroke is a leading cause of mortality and disability worldwide. However, existing models often fail to replicate key aspects of human pathophysiology, particularly blood–brain barrier (BBB) dysfunction and the salvageable ischemic penumbra. We developed a three-dimensional BBB chip model of acute ischemic stroke that reproduces penumbra-like, partially reversible BBB injury. This platform integrates a microfluidic BBB chip (Emulate) with parallel Transwell inserts to facilitate complementary structural, molecular, and functional analyses. Ischemia-like injury was induced using 2.5 μM antimycin A for 1 hour under oxygen-glucose deprivation conditions, followed by medium replacement to simulate reperfusion. Therapeutic hypothermia (33°C) was also applied during the reperfusion phase. The combination of reperfusion and hypothermia resulted in the most pronounced restoration of BBB integrity compared with reperfusion alone. The Emulate chip enabled structural evaluation of endothelial morphology, while the transwell model showed concordant recovery of BBB-related markers, including ZO-1 and VE-cadherin, along with decreased expression of the hypoxia-associated marker HIF-1α. This integrated platform enabled evaluation of BBB injury and recovery under ischemia- and reperfusion-like conditions. Our human cell-based 3D BBB stroke model captures key BBB-related features of penumbra-like injury and provides a human-relevant in vitro platform for investigating stroke pathophysiology and evaluating therapeutic strategies.